India : brief history of a civilization - Trautmann, Thomas R. (New Delhi : Oxford University Press, 2011)
In honor of Thomas R. Trautmann, American historian; papers presented at a conference on "Conceptualizing South Asia's past at Michigan", held at Ann Arbor during 5-6 October 2007.
Includes bibliographical references and index.
Keywords: India -- History -- Congresses; India, South -- History -- Congresses